2016
DOI: 10.1021/acsnano.5b07473
|View full text |Cite
|
Sign up to set email alerts
|

Size-Tuning Ionization To Optimize Gold Nanoparticles for Simultaneous Enhanced CT Imaging and Radiotherapy

Abstract: Computed tomography (CT) contrast and radiosensitization usually increase with particle sizes of gold nanoparticles (AuNPs), but there is a huge challenge to improve both by adjusting sizes under the requirements of in vivo application. Here, we report that AuNPs have great size-dependent enhancements on CT imaging as well as radiotherapy (RT) in the size range of 3-50 nm. It is demonstrated that AuNPs with a size of ∼13 nm could simultaneously possess superior CT contrast ability and significant radioactive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
175
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(181 citation statements)
references
References 51 publications
4
175
0
2
Order By: Relevance
“…151 Some published results indicated that great difference existed even with the same concentration of AuNPs with different size. 152 In 2016, Dou et al 153 explored and confirmed the distinctive size-dependent effects based on a series of spherical AuNPs for enhanced CT imaging and radiotherapy ( Figure 9). 153 The result indicated that AuNPs had great size-dependent enhancement on CT imaging and radiotherapy (RT) in the size range of 3-50nm.…”
Section: Aunms Based Imagingmentioning
confidence: 94%
See 1 more Smart Citation
“…151 Some published results indicated that great difference existed even with the same concentration of AuNPs with different size. 152 In 2016, Dou et al 153 explored and confirmed the distinctive size-dependent effects based on a series of spherical AuNPs for enhanced CT imaging and radiotherapy ( Figure 9). 153 The result indicated that AuNPs had great size-dependent enhancement on CT imaging and radiotherapy (RT) in the size range of 3-50nm.…”
Section: Aunms Based Imagingmentioning
confidence: 94%
“…152 In 2016, Dou et al 153 explored and confirmed the distinctive size-dependent effects based on a series of spherical AuNPs for enhanced CT imaging and radiotherapy ( Figure 9). 153 The result indicated that AuNPs had great size-dependent enhancement on CT imaging and radiotherapy (RT) in the size range of 3-50nm. Interestingly, AuNPs with asize of ∼13nm could simultaneously possess superior CT contrast ability and significant radioactive disruption.…”
Section: Aunms Based Imagingmentioning
confidence: 94%
“…Preoperative evaluation includes the condition of the whole body/organ and tumor (e.g., the shape, size, location, adjacent structures, tumor invasiveness, etc.). Gold NMs are proper candidates because of their high atomic number with a high attenuation coefficient and nontoxicity; [202][203][204][205] they can also reduce the dosage of contrast agents. However, with the advent of precision surgery era, intraoperative imaging technologies such as CAS cannot satisfy the need of accuracy, because of their limitations in detecting MRDs and real-time IGS.…”
Section: Preoperative Imaging For Precision Surgerymentioning
confidence: 99%
“…GNPs of 13 nm diameter were synthesized according to a previous report. 21 Initially, 150 mL of 2.2 mM Na 3 Ct$2H 2 O in deionized water was heated to 102 C.…”
Section: Synthesis Of Gnps-peg@cngrmentioning
confidence: 99%